Digitalisation, institutions and governance, and diffusion: Mechanisms and evidence - Claudio Baccianti; Vincent Labhard; Jonne Lehtimäki (European Central Bank (ECB), 2022)
Digitalisation can be described as a sequence of technology and supply shocks which affect the economy through employment and labour markets, productivity and output, and competition and market structure. This paper focuses on how digitalisation - the process of diffusion of digital technologies - is affected by institutions and governance. It discusses a number of theoretical mechanisms and empirical evidence for different sets of European and other countries. The results indicate that a higher quality of institutions is usually associated with both a greater speed of diffusion and a greater spread of digital technologies. The results also suggest that there are large, policy-relevant differences in the diffusion process depending on the level of development as well as the state of technological change of a country.
Keywords: E02; O11; O31; O33; O57; 330; technology; adoption; economy; estimates; panel